Correlation between Age, Nutritional Status, and Working Posture and Musculoskeletal Disorders in PT ARPS - Mufidha Khoirul Umami (Universitas Airlangga, 2019)
Introduction: Musculoskeletal disorders occur due to various factors: main factors, such as extortion of the muscles, repetitive activities, non-ergonomic working postures; secondary factors (pressure, vibrant, microclimate), and individual factors (age, years of service, sex, nutritional status, physical endurance, smoking habits, physical strength and anthropometry). The workers in the Injection Department at PT. ARPS mostly work with non-ergonomic working postures. The aim of this study is to analyze the correlation between age, nutritional status, and working postures and the complaints on musculoskeletal disorders among the workers in the Injection department at PT. ARPS. Metods: This study applies analytic observational method with a cross-sectional design. The sample is chosen by implementing simple random sampling with a total of 52 respondents. The data collection to measure the ratio risk level of the working postures of the injection workers is completed by using Rapid Upper Limb Assessment (RULA) measurement method, while Nordic Body Map (NBM) questionnaire form is used to measure risk level of the disorder, and anthropometry measurement is applied to evaluate the nutritional status of the workers, such as their height and weight. The data are analyzed using Spearman Rho’s Correlation (significance level α = 5%). Results: The percentage of injection workers are <35 years old (76.9%), have normal nutritional status (59.6%), 27 workers (51.9%) have low musculoskeletal disorders and 19 others (36.5%) have low-risk postures. Concluded: That there is a correlation between age (ρ-value = 0.005), nutritional status (ρ-value = 0.003) and working postures (ρ-value = 0.036) and musculoskeletal disorders on the injection workers at PT. ARPS. Keywords: injection worker, musculoskeletal disorders, Nordic Body Map, Rapid Upper Limb Assessement, working postures